In vitro antitrypanosomal and antioxidant activities of methanol extracts of selected Nigerian plants. Issue 1 (2nd January 2018) - Umar, Ismaila Alhaji; Ndidi, Uche Samuel; Abdullahi, Abdulmalik Salman; Ohilebo, Amos; Oluwafunminiyi, Emmanuel Taiye
ABSTRACT: The methanol extracts of Acacia albida (stem bark), Pericopsis laxiflora (leaves and stem bark), Artemisia absinthium (leaf), Gongronema latifolium (leaf), and Leptadenia hastata (leaf) were tested in vitro for antitrypanosomal and antioxidant properties. Stem bark extract of P. laxiflora was the most effective against the motility of the protozoans. Preliminary phytochemical analyses indicated the presence of cardiac glycosides and saponins in all extracts and the absence of anthraquinones. All extracts had terpenes except that from P. laxiflora stem bark; all extracts had flavonoids except those from A. albida and P. laxiflora stem barks. The methanol leaf extracts of A. absinthium and G. latifolium had the greatest flavonoids while the stem bark extract of P. laxiflora had the highest total phenol. The extracts demonstrated concentration-dependent antioxidant activity. P. laxiflora stem bark had the highest scavenging activity against 2, 2-diphenyl-1-picrylhydrazyl radical. A. albida, P. laxiflora, and A. absinthium had the greatest scavenging power against H2 O2 with EC50 of 0.92, 1.2, and 1.10 mg mL −1, respectively.